Advancements in multilingual and cross-lingual information retrieval : a study of lexical and reranking pipelines and their impact on effectiveness - Jeronymo, Vitor Amancio, 1993- (2023)
Orientadores: Roberto de Alencar Lotufo, Rodrigo Frassetto Nogueira